THE IMPACT OF CHANGES IN THE PUBLIC CATERING SYSTEM ON THE INCIDENCE OF SALMONELLOSIS AMONG THE POPULATION (The Conference Hub, 2025)
Currently, in various countries, the number of patients affected by salmonellosis continues to increase. According to WHO experts, salmonellosis remains a serious concern globally. The socio-economic damage caused by salmonellosis is significant. Experts note that even in countries with well-established epidemiological surveillance systems, official reports about the spread of salmonellosis often fail to reflect the actual situation due to limitations in bacteriological diagnostics. Such issues have been noted in numerous studies conducted in countries such as the UK, Spain, Austria, Bulgaria, Thailand, and Tasmania. The European Union has reported a growing trend in human salmonellosis cases since 2013, attributing this to a 57% increase in salmonellosis among poultry from 2013 to 2020.